A simple gelatin aerogel tablet sorbent for the effective vortex assisted solid phase extraction of polycyclic aromatic hydrocarbons from tea samples. (30th July 2022) - Myint Zaw, Myo; Poorahong, Sujittra; Kanatharana, Proespichaya; Thavarungkul, Panote; Thammakhet-Buranachai, Chongdee
Highlights: A gelatin aerogel tablet was simply developed and applied as a sorbent in a VA-SPE. Gelatin aerogel sorbent-based VA-SPE was developed to extract PAHs from tea samples. A proposed VA-SPE-HPLC-DAD sample preparation method is simple, rapid, and low cost. Good reusability and analytical performance were achieved in a real sample analysis. Abstract: A gelatin aerogel tablet was used as a vortex assisted solid phase extraction (VA-SPE) sorbent for the determination of polycyclic aromatic hydrocarbons (PAHs), benzo(a)anthracene (BaA), benzo(b)fluoranthene (BbF), and benzo(a)pyrene (BaP) in tea samples. They have been quantified by a high-performance liquid chromatography with a diode array detector (HPLC-DAD). The method shows good linearity (R 2  = 0.999) at concentrations of 5.00–200 ng L −1, with the limits of detection of 1.65 ± 0.02, 1.81 ± 0.02, and 2.06 ± 0.03 ng L −1 for BaA, BbF, and BaP, respectively. Good reproducibility (RSDs < 0.24%, n = 6), good precision (RSDs < 6.3%), and excellent reusability (n = 40, RSDs < 0.17%) were achieved. The tablet can extract PAHs within 1.5 min with good recoveries (70.10 ± 0.74% – 119.3 ± 4.1%). This method, which is simple, rapid, ecofriendly, and inexpensive, requires low consumption of organic solvent, and has potential application in food safety.